ASSESSING PROFIT EFFICIENCY OF ISLAMIC BANKS IN INDONESIA: AN INTERMEDIATION APPROACH - Bambang Agus Pramuka (Journal of Economics, Business, and Accountancy Ventura, 2011)
Islamic banking industry has been growing more rapidly. Beside, the increasing number of Islamic banks force the Indonesian banking sector to be more competitive, which results in better performance and higher efficiency of the Islamic banking Industry. This study investi- gates the profit efficiency of Islamic banks in Indonesia.  The Stochastic Frontier Approach (SFA) was adopted to evaluate monthly data released by full-fledged Islamic banks and Is- lamic window banks in Indonesia.  The period of observation was March 2003 until March2009.   The efficiency of Islamic banks was assessed by employing the intermediation ap- proach.  Hypotheses concerning the relationships of the input and output variables were pos- ited and tested.  The result of the study indicated those full-fledged banks are more efficient in generating profit than their counterpart, Islamic window banks.  The finding of this study highlights crucial information regarding the efficiency of Islamic banks in developing coun- try. Islamic banks should continuously increase the amount of third party fund and financing volume and make it more efficient in generating profit.  In addition, Islamic bank efficiency may have a great influence on the Indonesian government policy, which is expected to be in favor of the industrial sector instead of the monetary sector.